Endogenous On-the-job Search and Frictional Wage Dispersion - Matthias S. Hertweck (Verein für Socialpolitik, 2010)
This paper addresses the large degree of frictional wage dispersion in US data. The standard job matching model without on-the-job search cannot replicate this pattern. With on-the-job search, however, unemployed job searchers are more willing to accept low wage offers since they can continue to seek for better employment opportunities. This explains why observably identical workers may be paid very differently. Therefore, we examine the quantitative implications of on-the-job search in a stochastic job matching model. Our key result is that the inclusion of variable on-the-job search increases the degree of frictional wage dispersion by an order of a magnitude.
Keywords: E24; J31; J64; 330; Matching; On-the-job Search; Wage Dispersion